COVID-19 conspiracy belief and conceptions of democracy - Anne Küppers; Marion Reiser (Political Research Exchange)
Although conspiracy theories moved to the centre of the public debate during the Covid-19 pandemic and have severe consequences on politics and society, the link between Covid-19 conspiracy beliefs and democracy has hardly been scrutinized. By combining the literature on understandings and conceptions of democracy and the literature on upward conspiracy theories, we ask whether citizens who share Covid-19 conspiracy beliefs have a specific conception of democracy. Using data from a representative survey conducted in the East German Land of Thuringia in summer 2021 and by employing a fine-grained measure of attributes of democracy, we show that Covid-19 conspiracy belief is neither significantly associated with support for the idea of democracy nor with support for non-democratic forms of government. Instead, Covid-19 conspiracy believers have a particular understanding of democracy in which power is to be taken away from the political elites of representative democracy and more control is given to citizens.